Policy Legacies from Early Australian Telecommunications: A Private Sector Perspective - de Percy, Michael Alexander (Journal of Telecommunications and the Digital Economy, 2021)
The purpose of this article on the policy legacies from Australia’s early telecommunications history is not to present a counterfactual to Australia’s choice of public monopoly provision of early telecommunications services, but rather to indicate the extent that politics limited the private sector’s role in deploying early telegraph and telephone infrastructure in Australia. The article begins by outlining a theoretical framework for analysing government’s role in deploying new telecommunications technologies, before investigating some of the less familiar literature on the historical impact of government intervention on the private sector in the early Australian telegraph and telephone industries. It then discusses some of the political issues relating to the subsequent liberalisation of the telecommunications industry in Australia and concludes with a discussion of the historical legacies of government intervention on the private sector in the Australian telecommunications industry.